The Cheese Production Facility Microbiome Exhibits Temporal and Spatial Variability - Johnson, Jared; Curtin, Chris; Waite-Cusic, Joy (Frontiers in Microbiology, 2021)
A primary goal of modern cheese manufacturing is consistent product quality. One aspect of product quality that remains poorly understood is the variability of microbial subpopulations due to temporal or facility changes within cheese production environments. Therefore, our aim was to quantify this variability by measuring day-day and facility-facility changes in the cheese facility microbiome. In-process product (i.e. milk and cheese) and food-contact surfaces were sampled over the course of three production days at three cheese manufacturing facilities. Microbial communities were characterized using 16S rRNA metabarcoding and by plating on selective growth media. Each facility produced near-identical Cheddar cheese recipes on near-identical processing equipment during the time of sampling. Each facility also used a common pool of Lactococcus starter cultures which were rotated daily as groups of 4 to 5 strains and selected independently at each facility. Diversity analysis revealed significant facility-facility and day-day differences at each sample location. Facility differences were greatest on the food contact surfaces, explaining between 25 and 41% of the variance. Conversely, daily differences within each facility explained a greater proportion of the variance in the milk (20% versus 12%) and cheese (29% versus 20%). Further investigation into the sources of these differences revealed the involvement of several industrially relevant bacteria, including lactobacilli, which play a central role in flavor and texture development during Cheddar cheese ripening. Additionally, Streptococcus was found to contribute notably to differences observed in milk samples, whereas Acinetobacter, Streptococcus, Lactococcus, Exiguobacterium, and Enterobacteriaceae contributed notably to differences on the food contact surfaces. Facility differences in the cheese were overwhelmingly attributed to the rotation of Lactococcus starter cultures, thus highlighting circumstances where daily microbial shifts could be misinterpreted and emphasizing the importance of repeated measures. The outcomes of this work highlight the complexity of the cheese facility microbiome and demonstrate daily and facility-facility microbial variations which might impact cheese product quality.